Acute effects of an injury preventive warmup programme on unanticipated jump-landing-task performance in adult football players: A crossover trial. Issue 10 (3rd October 2022) - Friebe, David; Giesche, Florian; Niederer, Daniel; Ashigbi, Evans Y. K.; Groneberg, David A.; Banzer, Winfried
ABSTRACT: In football, unpredictable events (e.g. unexpected landings) seem to play a crucial role in the mechanism of non-contact knee injuries. This study investigated the effects of a single bout of an injury preventive warmup protocol on biomechanical landing stability and decision-making quality during preplanned and unanticipated jump-landings. A crossover study on 18 male amateur football players was performed. The participants completed a standard (ergometer) and an injury-preventive warmup protocol (Prevent injury and Enhance Performance (PEP)) on two different test days. After each protocol, participants performed countermovement jumps with preplanned (landing side displayed before takeoff) and unanticipated (landing side shown after takeoff) single-leg landings on a force plate. Outcomes were landing stability (height and time of the maximum vertical ground reaction force (pGRF), centre of pressure (CoP), the number of standing errors (ground contact with free leg)) and decision-making quality (landing error (wrong foot) count). Carry-over and crossover-tests were performed to find potential between-condition-differences. No carry-over effects occurred ( p > .05). The PEP led to a reduced CoP trace length (−18.4 ± 32.2%, p = .021) and earlier occurrence of pGRF (−4.72 ± 6.78%, p = .017) in the preplanned condition. No significant between-treatment-differences occurred within the unanticipated landings and decision-making quality ( p > .05). The primarily neuromuscular warmup protocol affects landing stability in the preplanned condition. However, it does not seem to better prepare football players for unpredictable events than a standard warmup. Trial registration: German Clinical Trials Register identifier: DRKS00016942. Highlights: Adapting movements rapidly to unanticipated external stimuli (e.g. unexpected landings) is crutial to prevent injuries in football It is unclear wether popular neuromuscular injury preventive warmup programmes (e.g. Prevent injury and Enhance Performance (PEP)) adaquatly prepare athletes for these situations Our study shows that the PEP warm up programme has acute effects on anticipated landing stability, but no influence on unanticipated landings or decision making quality Classic neuromuscular warm up programmes may not be the optimal choice to prepare athletes properly for the upcoming motor-cognitive demands in a football match